Working from Home and Commuting: Heterogeneity over Time, Space, and Occupations - Duco de Vos; Maarten van Ham; Evert J. Meijers (Institute of Labor Economics (IZA), 2019)
Teleworking may increase the willingness to accept a longer commute. This paper presents new evidence of the effect of teleworking on the length of commutes. We use novel panel data from the Netherlands, for the years 2008-2018, and find stronger effects compared to studies that use older data. Between 2008 and 2018 however, the effect was remarkably stable: workers that started teleworking increased their commutes by 12 percent on average. We analyse heterogeneity in the effect of teleworking on commuting across different levels of urbanization and across occupations. This study stresses the effects of teleworking on the geographical scale of labour markets, and provides important inputs for policymakers that aim to promote teleworking.
Keywords: R11; R41; O18; 330; telecommuting; commuting time; information technology; fixed effects